Young unemployed migrants in Iceland: Opportunities on the labour market and situations after the economic collapse with regard to work, social and financial aspects - Kristín Ása Einarsdóttir 1969- (2011)
The aim of this research is to see what factors impact on young unemployed migrants´ opportunities on the Icelandic labour market, and determine their situation after the economic collapse with relation to work, social and financial aspects. In this qualitative research interviews were taken with 14 people, including two focus groups with eleven unemployed migrants living in Iceland, and three individual interviews with specialists involved in migration issues. The results indicate that a limited ability in the Icelandic language is the factor that has the greatest impact on migrants´ opportunities on the Icelandic labour market. All interviewees placed particular emphasis on this matter. Additional factors such as prejudice, racism and negative media coverage are also linked to restricting opportunities on the labour market. It also appears that the situation concerning courses in Icelandic for foreigners is not good enough and official support to learn the language has been lacking in comparison with neighbouring countries. Results also indicate that after the economic collapse job requirements changed, with demands for good fluency in Icelandic becoming a necessity. Migrants have less chance of getting a job after the crisis hit than do Icelanders, with Icelanders rather hiring their compatriots. Moving back to the home country is not a solution, according to the participants, as the situation is no better there. The research shows that the situations of those migrants interviewed has changed for the worse after the economic collapse, based on the factors mentioned above.